ZnPc photosensitizer-loaded peony-shaped FeSe 2 remotely controlled by near-infrared light for antimycobacterial therapy - Peng Wu; Xiaoning Liu; Yuheng Duan; Liping Pan; Zhaogang Sun; Hongqian Chu; Chuanzhi Zhu; Bei Liu (Acta Materia Medica)
The development of novel antimicrobial agents is highly desirable for treating bacterial infections. Here, a smart photodynamic therapy (PDT) system based on a combination of peony-shaped ferroselite FeSe 2 particles and zinc (II) phthalocyanine (ZnPc) photosensitizers was constructed. Effective energy transfer occurred from ZnPc to FeSe 2 , because of their proximity, thus eliciting the OFF state of ZnPc photosensitizers. Under 808 nm NIR light irradiation, the photothermal effect of FeSe 2 promoted the release of ZnPc, thus turning on the photodynamic effect of the photosensitizers (ON state). In vitro, FeSe 2 -ZnPc exhibited high photo-to-thermal conversion efficiency (26.4%) and effective generation of reactive oxygen species for combined photothermal/photodynamic therapy. Therefore, the FeSe 2 -ZnPc hybrids have great potential to serve as alternatives to antibiotics for eradication of pathogenic bacteria.